Photoacoustic imaging for monitoring radiotherapy treatment response in head and neck tumors - Holzwarth, Niklas; Rachel, Zoë Elisa; Nölke, Jan-Hinrich; Schellenberg, Melanie; Bauer, Lukas; Schreck, Nicholas; Bender, Christoph J.; Dreher, Kris; Regnery, Sebastian; Kozyra, Katharina; Wiesenfarth, Manuel; Kopp-Schneider, Annette; et al. (Scientific reports, 2025)
Head and neck (HN) tumors are responsible for approximately 4% of annual new cancer cases worldwide. Besides surgery, radiochemotherapy, particularly fractionated radiotherapy (RT), is the gold-standard treatment modality for these cancers. However, there is currently no reliable early measure of success available to further personalize treatment plans. This work aims to address this critical bottleneck by pioneering the use of photoacoustic imaging (PAI) to measure treatment response in HN cancer patients undergoing RT. PAI leverages the photoacoustic effect in order to non-invasively recover functional tissue properties in depths of up to several centimeters. We hypothesized that oxygen saturation (sO2), hemoglobin concentration, and water content, as measured by PAI, would non-invasively reflect expected RT treatment effects, namely reoxygenation of lymph nodes (hypothesis H1), inflammation of surrounding organs (H2) and xerostomia (H3). Our study with n = 30 human subjects showed notable changes in sO2, hemoglobin concentration, and water levels in HN tumor patients resulting from disease treatment. Our data confirmed hypotheses H2 and H3, while an observed decrease in sO2 over the treatment course contradicted our prior assumptions (H1). A comprehensive analysis based on device and tissue digital twins, however, revealed that low blood volume fraction as encountered in malignant nodes, can lead to particularly high sO2 prediction errors, indicating that the measured sO2 values cannot be trusted within these regions. We conclude that our study is the first to show that PAI is capable of measuring early molecular changes induced by RT in human tissue non-invasively. Further studies are now needed to convert the potential of the new imaging technique into patient benefit.